Predominant V(H) genes expressed in innate antibodies are associated with distinctive antigen-binding sites - Seidl, Katherine J. (The National Academy of Sciences, 1999)
Antibodies to phosphatidylcholine (PtC), a common constituent of mammalian and bacterial cell membranes, represent a large proportion of the natural antibody repertoire in mice. Previous studies of several mouse strains (e.g., C57BL/6) have shown that anti-PtC antibodies are mainly encoded by the V(H)11 and V(H)12 immunoglobulin heavy chain variable region gene families. We show here, however, that V(H)11 and V(H)12 encode only a small proportion of the anti-PtC antibodies in BALB/c mice. Instead, V(H)Q52-encoded antibodies predominate in this strain. In addition, two-thirds of the cells expressing V(H)Q52 family genes use a single gene (which, interestingly, has been previously shown to predominate in the anti-oxazolone response). We also show here that in anti-PtC antibodies from all strains, the distinctive antigen-binding sites associated with V(H)Q52 differ substantially from those associated with V(H)11 and V(H)12. That is, V(H)Q52-containing transcripts preferentially use the joining region J(H)4 rather than J(H)1 and exhibit more diverse complementarity-determining region 3 (CDR3) junctions with more N-region nucleotide additions at the gene segment junctions. Thus, the V(H) gene family that predominates in the anti-PtC repertoire differs among mouse strains, whereas the distinctive V(H)DJ(H) rearrangements (CDR3, J(H)) associated with each V(H) gene family are similar in all strains. We discuss these findings in the context of a recent hypothesis suggesting that CDR3 structure, independent of V(H) framework, is sufficient to define the specificity of an antibody.